Analisis Sistem Informasi Akuntansi Account Payable dalam Pembayaran Hutang Vendor di Hotel Swiss-Belinn Airport Surabaya - Redyvastyo Ari Nurogo; Lia Nirawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to analyze the Account Payable Accounting Information System in paying debts to vendors. It utilizes a qualitative descriptive method with data collection through observation, interviews, and documentation. Hotel Swiss-Belinn Airport Surabaya implements credit payments by deferring payment until the agreed-upon date, but the risk of accumulating debts arises if payments are not made on time. The debt payment process involves warehouse, purchasing, receiving, and accounting functions, utilizing the Carmen system connected to Protel to record debts. Documents required by Account Payable include Purchase Requisition, Purchase Order, Receiving Report, Sales Invoice, Tax Invoice, Bank Payment Voucher, and Receipt. Payment methods involve both cash and credit payments through transfers. Challenges faced by Account Payable include discrepancies between user orders and vendor deliveries. Suggestions to improve efficiency include enhancing communication with users and monitoring vendors.